Perilaku Caring Perawat dengan Kepatuhan Minum Obat Anti Tuberkulosis pada Pasien TB Paru - Ledy Rahmawati Hamzah; Sri Andriani Ibrahim; Rachmawaty D. Hunawa (Journal of Telenursing (JOTING), 2026)
This study aimed to determine the relationship between nurses' caring behavior and adherence to taking anti-tuberculosis medication among pulmonary tuberculosis patients at Tilango Public Health Center, Gorontalo Regency. This study employed a quantitative method with a correlational design using a cross-sectional approach. The results showed a significant relationship between nurses' caring behavior and adherence to taking anti-tuberculosis medication among pulmonary tuberculosis patients, with a p-value of 0.019 (p < 0.05) and a weak correlation strength. The conclusion of this study is that there is a relationship between nurses' caring behavior and adherence to taking anti-tuberculosis medication among pulmonary tuberculosis patients at Tilango Public Health Center, Gorontalo Regency.   Keywords: Medication Adherence, Nurses' Caring Behavior, Pulmonary Tuberculosis